PERAN MEDIA SOSIAL SEBAGAI BENTUK INTERAKSI ANTARA TEKNOLOGI DAN CALON MAHASISWA DALAM PROMOSI UNIVERSITAS ROYAL - Ridwan, Ridwan; Iqbal, Muhammad (Smart Education, 2026)
Abstract: The increasingly competitive landscape among private universities in Indonesia requires innovative and digital-based promotion strategies that align with the behavior of the younger generation. This study explores social media as a promotional medium, focusing on Royal University. Using a qualitative descriptive approach, data were collected through in-depth interviews, documentation of digital content, and observation of audience interaction on Instagram and TikTok. The findings reveal that the campus adopts a content-based marketing and engagement-driven strategy. Creative, informative, and relatable content is prioritized to build audience connection. Posts that receive the highest engagement include videos of student activities, scholarship announcements, and alumni testimonials. Audience responses are generally positive, with most prospective students expressing satisfaction with the promotional content provided. These results highlight the strong potential of social media as an effective tool for promoting higher education when managed strategically and sustainably. The study contributes both theoretically and practically: it enriches the understanding of digital marketing in higher education and provides guidance for private universities in developing impactful communication strategies. Future research is recommended to employ mixed methods with quantitative analysis to measure the effectiveness of digital promotional content in attracting prospective students. Keywords: Promotional Strategy, Social Media, Digital Marketing, Royal University. Abstrak: Lanskap yang semakin kompetitif di antara perguruan tinggi swasta di Indonesia membutuhkan strategi promosi inovatif dan berbasis digital yang selaras dengan perilaku generasi muda. Penelitian ini mengeksplorasi media sosial sebagai media promosi, dengan fokus pada Universitas Royal. Dengan menggunakan pendekatan deskriptif kualitatif, data dikumpulkan melalui wawancara mendalam, dokumentasi konten digital, dan pengamatan interaksi audiens di Instagram dan TikTok. Temuan ini mengungkapkan bahwa kampus mengadopsi pemasaran berbasis konten dan strategi berbasis keterlibatan. Konten yang kreatif, informatif, dan relatable diprioritaskan untuk membangun koneksi audiens. Postingan yang menerima keterlibatan tertinggi termasuk video kegiatan mahasiswa, pengumuman beasiswa, dan testimoni alumni. Tanggapan audiens umumnya positif, dengan sebagian besar calon siswa menyatakan kepuasan dengan konten promosi yang disediakan. Hasil ini menyoroti potensi kuat media sosial sebagai alat yang efektif untuk mempromosikan pendidikan tinggi jika dikelola secara strategis dan berkelanjutan. Studi ini berkontribusi baik secara teoritis maupun praktis: memperkaya pemahaman pemasaran digital di pendidikan tinggi dan memberikan panduan bagi universitas swasta dalam mengembangkan strategi komunikasi yang berdampak. Penelitian kedepan dianjurkan untuk menggunakan metode campuran dengan analisis kuantitatif untuk mengukur efektivitas konten promosi digital dalam menarik calon mahasiswa. Kata Kunci : Strategi Promosi, Media Sosial, Digital Marketing, Universitas Royal